Nanocomposites and Nanohybrids in Additive Manufacturing - Ertürk, A.T.; Özer, G. (De Gruyter, 2023)
Additive manufacturing (AM) has undergone significant technological development since its emergence in the 1970s. This development is expected to continue and take an important place in the manufacturing sector. Developing new materials for AM processes is among today’s essential issues. This chapter gives general insight into the application of nanocomposites and nanohybrids in the AM. AM has become very common in the last few years, with its benefits to high-tech products and its superior features such as enabling the production of end products. Additive manufacturing is used in many areas such as defense industry, automotive, medicine, biomedical, biomedical engineering, and medical/pharmaceutical industries. In particular, it is not possible to produce some specific products by traditional methods. On this point, AM technologies have become quite advantageous. The content presents recent advances and classification of 3D printing processes for nanocomposites. These include high-performance polymer, and metal and ceramic nanocomposites, which are expected to expand into applications requiring highly durable materials suitable against extreme conditions. Input material properties, as well as the processing parameters for AM processes of nanocomposites and nanohybrids, are explained. General information for the mechanical properties of the AM components made of nanocomposites and nanohybrids is presented.
Keywords: Additive Manufacturing (AM); Nanocomposites (NCs); Nanohybrids (NHs); Polymer Nanoparticles (PNPs); Metal Nanoparticles (MNPs); Ceramic Nanoparticles (CNPs)